Perceptions of effectiveness and performance evaluation in Hungarian higher education in the Carpathian Basin - Pallay, Katalin; Demeter-Karászi, Zsuzsanna; Pusztai, Gabriella (Central European Journal of Educational Research, 2025)
Several international studies have addressed the quantitative and qualitative changes in higher education participation and the impact of the evaluative state and institutional quality management on higher education societies (Altbach, 2000; Altbach, 2002; Kwiek & Antonowicz, 2015). However, despite the relatively rich research in higher education in our region, the impact of higher education performance evaluation on the views of faculty members has not been investigated. In our study, we investigate the types of performance evaluation that are typical in higher education in the Carpathian Basin and provide a picture of the perceptions of faculty members on performance evaluation. We will examine the differences and similarities in performance evaluation across the different types of performance. Our research questions concern their homogeneity and interrelationships. We conducted a hybrid coding analysis of the transcripts of qualitative focus group interviews with faculty members in one of the most eastern regions of the European Higher Education Area (EHEA), using data from 2022 on the impact of the introduction of performance evaluation in higher education. The main findings of the study show that faculty members' views on performance show high diversity. There is a correlation in views on performance evaluation, but they are not exclusive. The points to consider in the context of performance evaluation can provide guidance for decision-makers in higher education.